Regional techniques and novel local anesthetics in ambulatory anesthesia: ambulatory anaesthesia - Horning, Audrey; Frietsch, Thomas; Horn, Jean-Louis (Current opinion in anaesthesiology, 2025)
Purpose of review  - In an economically strained healthcare system, regional anesthesia is often perceived as an excessive cost by potentially delaying surgery and reducing operating room output; however, when integrated effectively, regional anesthesia can enhance efficiency, reduce costs, and expand access to ambulatory surgery for high-risk patients. - Findings  - This review summarizes practical strategies - such as walking spinal anesthesia with short-acting agents (e.g. chloroprocaine and prilocaine) and ultrasound-guided peripheral nerve blocks - based on experience from a high-volume university outpatient center. Topics include patient selection, procedural efficiency, risk mitigation (e.g. urinary retention and transient neurological symptoms), discharge protocols, and the use of continuous catheters for extended pain control. - Summary  - When correctly used, regional anesthesiology improves patient satisfaction, supports rapid recovery, and enables safe outpatient care even in medically complex cases.
Gesehen am 01.12.2025